(untitled) (Jóvenes en la Ciencia, 2024)
The purpose of the article is to explore the potential impact of artificial intelligence on the future of humanity, including both its benefits and challenges. The article discusses the ways in which AI could affect the human race, including its potential to augment human intelligence, improve healthcare delivery, and create new roles and jobs. It also addresses concerns about human agency, evolution, and survival, and the need for solutions to ensure a better-trained and healthier workforce. The article provides insights into the potential benefits and drawbacks of AI, as well as solutions to ensure that AI is used in a way that benefits humanity. It emphasizes the need for AI to augment human intelligence, rather than replace it, and highlights the potential for AI to significantly improve usability and access to technology. The article also includes quotes from experts in the field, providing a well-rounded perspective on the topic.